Konservatisma Akuntansi Sebagai Pemicu Gejala Timbulnya Sengketa Pajak Penghasilan Badan - Dian Esha Putri, I Gusti Ayu; Noviari, Naniek (E-Jurnal Akuntansi, 2013)
This study aimed to observe the effect of accounting conservatism on the onset of symptoms of income tax disputes. This study was conducted on services companies listed on the Indonesia Stock Exchange. Data analysis method used is a simple linear regression analysis. The study used three regression models because the variable Y (symptoms of income tax disputes) is proxied by three ratio, there are AR/AP, CR/CD and Sales/Expense. While the variable X (accounting conservatism) is proxied by accrual. Based on the analysis and hypothesis testing, all the three regression models show that accounting conservatism gave positif effect on the onset of symptoms of income tax disputes. This shows that the higher conservatism adopted by the company, the higher incidence of symptoms of income tax disputes at the company as well. Keywords:      Accounting Conservatism, Symptoms of Income Tax Disputes, Services Company.